2010
DOI: 10.1021/la9040979
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Synthesized Ormosils with Application to Stone Restoration

Abstract: A challenging objective in monumental stone restoration is to synthesize crack-free silica materials for application as consolidants. Hydrophobicity is also a valuable property for such products; it is important to prevent the penetration of water because water is the main vehicle by which the agents of decay enter the pore structure of the stone. We report the development of a hydrophobic crack-free nanomaterial with application to stone restoration. Specifically, organically modified silicate (ormosil) has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 30 publications
4
124
0
3
Order By: Relevance
“…Also, we observed that the hydrophobicity of the paper substrate is stable and there is no significant change in the contact angle even after 25 cycles of bending (bending radius is 2.5 mm). Fig.9b shows the contact angle of the films is stable over the whole pH range (pH [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. There is a slight decrease (6 ) in the contact angle at pH 14 but still the surface is hydrophobic with a contact angle of 117 .…”
Section: Hydrophobicity Of Nanoporous Filmsmentioning
confidence: 99%
“…Also, we observed that the hydrophobicity of the paper substrate is stable and there is no significant change in the contact angle even after 25 cycles of bending (bending radius is 2.5 mm). Fig.9b shows the contact angle of the films is stable over the whole pH range (pH [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. There is a slight decrease (6 ) in the contact angle at pH 14 but still the surface is hydrophobic with a contact angle of 117 .…”
Section: Hydrophobicity Of Nanoporous Filmsmentioning
confidence: 99%
“…The advancing and receding contact angles were measured using the ARCA (Advancing and Receding Contact Angles) method included in the equipment software (OCA 15 plus), with the volume of the droplet being increased/decreased by 5 µL. Details of this procedure are given in a previous paper [10].…”
Section: Effectiveness On Quarry Stonementioning
confidence: 99%
“…In the last years, we have prepared crack-free nanomaterials for stone conservation [7][8][9][10][11][12][13][14][15][16][17][18]. Specifically, the addition of an aqueous solution of n-octylamine to an alkoxysilane produces inverse micelles, which act as nanoreactors, generating silica seeds.…”
Section: Introductionmentioning
confidence: 99%
“…For pure silica xerogel, there are absorption bands observed at around 3450 cm −1 , 2964 cm −1 , 1630 cm −1 , 1090 cm −1 , 954 cm −1 , and 800 cm −1 . The broad absorption band at around 3450 cm −1 is attributed to Si-OH bonds or absorbed water [16,17]. The three peaks around 2964 cm −1 corresponds to the stretching vibration of C-H bonds from -CH3 [18].…”
Section: Ftir Characterizationmentioning
confidence: 99%